PENGARUH MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA SMP N 1 X KOTO DIATAS - Dewi Fitri Yeni; Septia Lasia Putri; Merika Setiawati (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
Motivated by a lack of motivation student learning action in participating in social science learning and the learning outcomes obtained by students have not been maximized. The purpose of this research is (1) to determine the effect of learning motivation on student learning outcomes in social studies subjects for class Vll students of SMP Negeri 1 X Koto (2) to determine the magnitude of the relationship between learning motivation and learning outcomes in social studies subjects for grad  VII students of SMP Negeri 1 X Koto Above. This type of research was qualitative with a sample of all grade’s VII studentsof SMP Negeri 1 X Koto Above as many as 31 students. Data collection techniques using questionnaires and data analysis techniques using simple linear regression techniques.  The results of this study are a positive and significant relationship between the effect of providing motivation on student learning outcomes in class Vll SMP Negeri 1 X Koto. This is evidenced by the results of the analysis obtained rcount = 0.44. Keywoard: motivation , learning outcomes , students